The unconscious is structured like an archive “Epic” politics and postmodernity in Indonesian cinema - Yngvesson, Dag (2018)
Access online through this link: https://www.plarideljournal.org/article/the-unconscious-is-structured-like-an-archive-epic-politics-and-postmodernity-in-indonesian-cinema
Keywords: Motion pictures -- Indonesia; Postmodernism; Film criticism